2020
DOI: 10.1002/anie.201916613
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetically Inspired Syntheses of Secu′amamine A and Fluvirosaones A and B

Abstract: Presented here is a concise synthesis of secu′amamine A, and fluvirosaones A and B from readily available allosecurinine and viroallosecurinine. The key C2‐enamine derivative of (viro)allosecurinine, the presumed biosynthetic precursors of these natural products, was accessed, for the first time, by a VO(acac)2‐mediated regioselective Polonovski reaction. Formal hydration and 1,2‐amine shift of this pluripotent enamine compound afforded secu′amamine A. Formal oxidative [3+2] cycloaddition reaction between this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“…Consistent with the original proposal by Magnus [23] and the synthetic verification by us, [24] C3‐alcohol derivative 167 is the plausible biosynthetic precursor of secu'amamine A ( 24 ). It is likely that (3 S )‐3‐hydroxyallosecurinine ( 138 ), a potential natural product yet to be discovered, undergoes a 1,2‐amine shift for the biosynthesis of secu'amamine A ( 24 ).…”
Section: Biosynthetic Hypothesissupporting
confidence: 79%
See 4 more Smart Citations
“…Consistent with the original proposal by Magnus [23] and the synthetic verification by us, [24] C3‐alcohol derivative 167 is the plausible biosynthetic precursor of secu'amamine A ( 24 ). It is likely that (3 S )‐3‐hydroxyallosecurinine ( 138 ), a potential natural product yet to be discovered, undergoes a 1,2‐amine shift for the biosynthesis of secu'amamine A ( 24 ).…”
Section: Biosynthetic Hypothesissupporting
confidence: 79%
“…For the biosynthesis of fluvirosaones A ( 4 ) and B ( 28 ), we propose that enamine 166 undergoes a stereodivergent formal [3+2] cycloaddition reaction with an external three‐carbon unit. Our synthetic studies showed that the configuration at C2 determines the fate of 1,2‐amine shift in that 2‐ epi ‐fluvirosaone A ( 148 ) undergoes immediate rearrangement to fluvirosaone B ( 28 ) [24] . We postulate that an analogous stereodivergent biosynthetic process is operative in vivo .…”
Section: Biosynthetic Hypothesismentioning
confidence: 76%
See 3 more Smart Citations